Evaluation of atlas‐based auto‐segmentation software in prostate cancer patients. Issue 3 (6th August 2014) - Greenham, Stuart; Dean, Jenna; Fu, Cheuk Kuen Kenneth; Goman, Joanne; Mulligan, Jeremy; Tune, Deanna; Sampson, David; Westhuyzen, Justin; McKay, Michael
Abstract Introduction The performance and limitations of an atlas‐based auto‐segmentation software package (ABAS; Elekta Inc.) was evaluated using male pelvic anatomy as the area of interest. Methods Contours from 10 prostate patients were selected to create atlases in ABAS. The contoured regions of interest were created manually to align with published guidelines and included the prostate, bladder, rectum, femoral heads and external patient contour. Twenty‐four clinically treated prostate patients were auto‐contoured using a randomised selection of two, four, six, eight or ten atlases. The concordance between the manually drawn and computer‐generated contours were evaluated statistically using Pearson's product–moment correlation coefficient (r) and clinically in a validated qualitative evaluation. In the latter evaluation, six radiation therapists classified the degree of agreement for each structure using seven clinically appropriate categories. Results The ABAS software generated clinically acceptable contours for the bladder, rectum, femoral heads and external patient contour. For these structures, ABAS‐generated volumes were highly correlated with 'as treated' volumes, manually drawn; for four atlases, for example, bladder r = 0.988 (P < 0.001), rectum r = 0.739 (P < 0.001) and left femoral head r = 0.560 (P < 0.001). Poorest results were seen for the prostate (r = 0.401, P < 0.05) (four atlases); however this was attributed to the comparison prostate volume being contoured on magnetic resonance imaging (MRI) rather than computed tomography (CT) data. For all structures, increasing the number of atlases did not consistently improve accuracy. Conclusions ABAS‐generated contours are clinically useful for a range of structures in the male pelvis. Clinically appropriate volumes were created, but editing of some contours was inevitably required. The ideal number of atlases to improve generated automatic contours is yet to be determined.